SPATIAL DIFFERENCES OF VARIATIONS OF POWER FREQUENCY MAGNETIC FIELD IN ARARAT SEISMIC POLYGON (Proceedings of the YSU C: Geological and Geographical Sciences, 2014)
In the present work the methodological errors conditioned by the spatial gradient and difference of variation of magnetic fields are observed. It has been found that these errors are not connected with the accuracy or sensitivity of the apparatus. If it is granted that the expected tectonomagnetic effect is several nTl, thеn the attempts to discover it may be considered impossible.
Keywords: Аrarat seismic polygon; tectonomagnetic effect; variations of EMF